Uma análise do déficit habitacional nos municípios cearenses - Gomes, Agláio Soares (2014)
The National Housing Policy (NHP), approved on 2004, aims to resume planning process for the housing sector and ensure new institutional conditions to promote access to decent housing for all segments of the population. The implementation of the NHP presupposes the creation of a National Housing System (NHS) as an instrument to, at once, neatly directs the efforts of agents involved with the issue of housing, around a common and urgent purpose, which is the availability of housing units for all social levels. In this context, this work aims to determine the impact of investments on housing and socioeconomic variables on all Ceará state deficit, for the year 2010. Was identified the necessity of increasing the investments on housing and urban infrastructure to reduce housing deficit on Ceará state.